Electromagnetic-shielding high-thermal-conductivity underfill adhesive and preparation method thereof

By using core-shell structural particles coated with conductive polymers and thermally conductive inorganic fillers in chip packaging, and combining epoxy resin and other materials to prepare electromagnetic shielding high-thermal bottom fillers, the problems of electromagnetic interference and thermal management in chip packaging are solved, and the problem of electromagnetic interference and thermal management is achieved. Efficient electromagnetic shielding and thermal management.

CN119286444APending Publication Date: 2025-01-10WANHUA CHEM GRP CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411514241.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing electromagnetic shielding and heat dissipation solutions cannot effectively meet the needs of the chip package, resulting in electromagnetic interference and thermal management problems, affecting the performance and reliability of the chip.

Method used

The shielding particles with conductive polymer as the shell and thermally conductive inorganic filler as the core material are chemically coated to form a core-shell structure, and the electromagnetic shielding high thermal conductivity bottom filler is prepared by combining epoxy resin and other materials. The high thermal conductivity bottom filler is formed through the stirring and curing process. Underfill glue with dielectric constant and high dielectric loss.

Benefits of technology

It realizes electromagnetic shielding, high thermal conductivity and insulation, improves the chip's electromagnetic interference resistance and thermal management performance, and has high dimensional stability, high temperature resistance and high fluidity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005106263080000111
    Figure BDA0005106263080000111
  • Figure BDA0005106263080000121
    Figure BDA0005106263080000121
  • Figure FDA0005106263070000011
    Figure FDA0005106263070000011
Patent Text Reader

Abstract

The invention belongs to the technical field of adhesives, and mainly relates to an electromagnetic-shielding high-thermal-conductivity underfill adhesive and a preparation method thereof. The electromagnetic-shielding high-thermal-conductivity underfill adhesive is mainly prepared from the following raw materials in parts by weight: 10-30 parts of epoxy resin; 1-10 parts of a diluent; 0.1 to 2 parts of pigment; 0.1 to 2 parts of a coupling agent; 10-30 parts of a curing agent; 0.1 to 5 parts of an accelerant; 30 to 60 parts of filler; 0-40 parts of shielding particles A; 0-40 parts of shielding particles B; and the shielding particles are prepared by coating a heat-conducting inorganic filler with a conductive polymer to form a core-shell structure. The underfill adhesive disclosed by the invention has the characteristics of high dielectric constant, high dielectric loss, electromagnetic interference resistance, high thermal conductivity, high dimensional stability, high temperature resistance and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to an electromagnetic shielding high-thermal-conductivity bottom filling adhesive and a preparation method thereof, belonging to the technical field of adhesives. Background Art

[0002] With the rapid development of technologies such as artificial intelligence, big data, and 5G, the semiconductor industry's requirements for chip performance are constantly increasing. As the basic building block of a chip, the number and density of transistors are directly related to the performance and power consumption of the chip. The economic benefits of Moore's Law have encountered a bottleneck, and chip manufacturing has entered the post-Moore era. Moore's Law refers to the fact that with the upgrade of technology, the number of transistors carried by a chip will double every 18-24 months, while the performance will double or the cost will be halved. With the evolution of chip technology, the R&D cycle will be lengthened, and it will take longer to iterate the process technology. Due to the limitations of physical limits at the microscopic level, the rate of decline in the cost of a unit transistor continues to slow down. From 16nm to 10nm, the cost of every billion transistors has decreased by 23.5%, but from 5nm to 3nm, the cost has only decreased by 4%. If the chip process is miniaturized to nearly 1nm, it will enter the field of quantum physics, resulting in problems such as short channel effects and heat dissipation that need to be solved, making Moore's Law gradually invalid. With the rising cost of advanced processes and the increasing difficulty of technology upgrades, advanced packaging such as multi-layer stacking, heterogeneous integration, and SIP system-level packaging are seen as important ways to continue Moore's Law.

[0003] System reconstruction through advanced packaging and SIP system-level packaging can reduce space occupancy, integrate more components and functions into a smaller space, and improve the functional density of the chip. However, with the increase in chip density, the problems of electromagnetic interference and thermal management are becoming increasingly apparent. The current electromagnetic shielding and heat dissipation solutions mostly act on the outside of the package and cannot effectively meet the needs of the inside of the package. In a short period of time in a local space, when a large current passes through, the signal interference caused by the electromagnetic waves generated thereby affects the precision and accuracy of the electronic equipment. At the same time, the power loss of the chip will be converted into heat, which can easily cause the local temperature to rise rapidly and cause thermal failure of the chip. Therefore, solving electromagnetic interference and thermal failure in packaging is of great significance to the technological progress of the entire semiconductor industry. Summary of the invention

[0004] In view of the above problems in the prior art, the present invention provides an electromagnetic shielding high thermal conductivity bottom filling glue and a preparation method thereof.

[0005] The technical solution of the present invention to solve the above technical problems is as follows:

[0006] One of the purposes of the present invention is to provide an electromagnetic shielding high thermal conductivity bottom filling adhesive, which is mainly prepared from the following raw materials in parts by weight:

[0007] 10-30 parts of epoxy resin, for example 10, 12, 14, 16, 18, 19, 20, 23, 25, 28 parts;

[0008] 1-10 parts of diluent, for example 1, 2, 3, 4, 5, 6, 7, 8, 9, 10 parts;

[0009] Pigment 0.1-2 parts, for example 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.2, 1.5, 1.8 parts;

[0010] 0.1-2 parts of coupling agent, for example 0.1, 0.3, 0.5, 0.7, 0.9, 1, 1.2, 1.5, 1.8 parts;

[0011] 10-30 parts of curing agent, for example 10, 12, 14, 16, 18, 19, 20, 23, 25, 28 parts;

[0012] 0.1-5 parts of accelerator, for example 0.1, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 parts;

[0013] 30-60 parts of filler, for example 30, 35, 40, 45, 50, 55, 60 parts;

[0014] Shielding particles A 0-40 parts, for example 0, 1, 3, 5, 10, 15, 20, 25, 30, 35 parts;

[0015] Shielding particles B 0-40 parts, for example 0, 1, 3, 5, 10, 15, 20, 25, 30, 35 parts;

[0016] And the shielding particles A and B are not 0 at the same time

[0017] The shielding particles A and shielding particles B are particles with a core-shell structure formed by chemical coating, using a conductive polymer as a shell and a thermally conductive inorganic filler as a core material.

[0018] In some specific embodiments, the preparation of the shielding particles A comprises the following steps:

[0019] (1) adding aminosilane to solvent A, stirring to dissolve, then heating, adding thermally conductive inorganic filler A, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a surface-treated thermally conductive inorganic filler A;

[0020] (2) adding the thermally conductive inorganic filler A treated in step (1) to the aqueous solution of solvent A, stirring, continuing to add pyrrole monomer, and cooling to below 10° C.;

[0021] (3) preparing a catalyst solution, adding it to the solution of step (2), continuing the reaction, and filtering, washing, and drying after the reaction to obtain shielding particles A;

[0022] The thermally conductive inorganic filler A is at least any one of aluminum oxide, magnesium oxide, aluminum nitride, and boron nitride.

[0023] In some preferred embodiments, the preparation of the shielding particles A comprises the following steps:

[0024] (1) adding aminosilane to solvent A, stirring and dissolving at room temperature, then heating to 50-80° C., adding thermally conductive inorganic filler A, stirring and reacting for 60-120 min, filtering, washing, and drying after the reaction to obtain a surface-treated thermally conductive inorganic filler A;

[0025] (2) adding the thermally conductive inorganic filler A treated in step (1) to the aqueous solution of solvent A, stirring, continuing to add pyrrole monomer, and cooling to below 10° C.;

[0026] (3) preparing a catalyst solution, adding it to the solution of step (2), and continuing the reaction for 12-24 hours. After the reaction is completed, filtering, washing, and drying to obtain shielding particles A;

[0027] The thermally conductive inorganic filler A is at least any one of aluminum oxide, magnesium oxide, aluminum nitride, and boron nitride.

[0028] Wherein, the solvent A is an organic solvent, such as common alcohol solvents, acetone, dichloromethane, toluene, etc., preferably ethanol. Solvent A mainly plays the role of dispersion and dissolution. Those skilled in the art can add the corresponding amount according to experience, without particular limitation. The catalyst solution in step (3) is a trivalent iron salt solution, such as a ferric chloride solution, and specifically, the amount of ferric chloride catalyst added is 3%-10% of the solution in step (2).

[0029] In some more preferred embodiments, the preparation of the shielding particles A comprises the following steps:

[0030] (1) Add 2-8 g of aminosilane to 100 ml of ethanol solution, stir at a temperature of 20-40° C. for 20-60 min, continue to heat to 50-80° C., add 5-20 g of thermally conductive inorganic filler, stir for 60-120 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0031] (2) adding 10 g of the filler treated in step (1) into 500 ml of 25% ethanol aqueous solution, stirring for 10-30 min, adding 5-10 g of pyrrole monomer, and cooling in an ice water bath to below 10° C.;

[0032] (3) Take 3-10 g of anhydrous ferric chloride, add it to 100 ml of water to dissolve, add it to the solution of step (2), react for 12-24 hours, filter, wash and dry after the reaction to obtain shielding particles A;

[0033] The thermally conductive inorganic filler is one of aluminum oxide, magnesium oxide, aluminum nitride and boron nitride.

[0034] In some specific embodiments, the preparation of the shielding particles B comprises the following steps:

[0035] (1) adding aminosilane to solvent A, stirring to dissolve, then heating, adding thermally conductive inorganic filler B, stirring to react, filtering, washing, and drying after the reaction is completed to obtain a surface-treated thermally conductive inorganic filler B;

[0036] (2) adding the thermally conductive inorganic filler B treated in step (1) to the aqueous solution of solvent B, stirring, continuing to add aniline monomer, cooling to below 10° C., and stirring for reaction;

[0037] (3) preparing a catalyst solution, adding it to the solution of step (2), continuing the reaction, and filtering, washing, and drying after the reaction to obtain shielding particles B;

[0038] The thermally conductive inorganic filler B is at least one of aluminum nitride and boron nitride.

[0039] In some preferred embodiments, the preparation of the shielding particles B comprises the following steps:

[0040] (1) adding aminosilane to solvent A, stirring and dissolving at room temperature, then heating to 50-80° C., adding thermally conductive inorganic filler B, stirring and reacting for 60-120 min, filtering, washing and drying after the reaction, and obtaining a surface-treated thermally conductive inorganic filler B;

[0041] (2) adding the thermally conductive inorganic filler B treated in step (1) to the aqueous solution of solvent B, stirring, continuing to add aniline monomer, cooling to below 10° C., and stirring for reaction;

[0042] (3) preparing a catalyst solution, adding it to the solution of step (2), and continuing the reaction for 12-24 hours. After the reaction is completed, filtering, washing, and drying to obtain shielding particles B;

[0043] The thermally conductive inorganic filler B is at least one of aluminum nitride and boron nitride.

[0044] Wherein, the solvent A is an organic solvent, such as common alcohol solvents, acetone, dichloromethane, toluene, etc., preferably ethanol. Solvent A mainly plays the role of dispersion and dissolution. Those skilled in the art can add the corresponding amount according to experience without special restrictions. Solvent B is mainly used to disperse the thermally conductive inorganic filler B, usually an aqueous sulfuric acid solution, and its concentration is not particularly limited, for example, 1 mol / L. The catalyst solution in step (3) is a persulfate solution, such as an ammonium persulfate solution. Specifically, the amount of ammonium persulfate catalyst added is 8%-15% of the solution in step (2).

[0045] In some more preferred embodiments, the preparation of the shielding particles B mainly comprises the following steps:

[0046] (1) Add 2-8 g of aminosilane to 100 ml of ethanol solution, stir at a temperature of 20-40° C. for 20-60 min, continue to heat to 50-80° C., add 5-20 g of thermally conductive inorganic filler, stir for 60-120 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0047] (2) adding 10 g of the filler treated in step (1) to 100 ml of 1 mol / L sulfuric acid aqueous solution, stirring for 3-10 min, adding 5-10 g of aniline monomer, cooling to below 10° C. in an ice water bath, and stirring for 20-40 min;

[0048] (3) taking 8-15 g of ammonium persulfate and dissolving it in 100 ml of sulfuric acid aqueous solution, adding it to the solution of step (2), reacting for 12-24 h, filtering, washing, and drying after the reaction to obtain shielding particles B;

[0049] The thermally conductive inorganic filler is one of aluminum nitride and boron nitride.

[0050] In some more preferred embodiments, the preparation of the shielding particles B mainly comprises the following steps:

[0051] (1) Add 5 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to 100 ml of ethanol solution, stir at 25° C. for 30 min, continue to heat to 60° C., add 10 g of thermally conductive inorganic filler, stir for 90 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0052] (2) adding 10 g of the filler treated in step (1) to 100 ml of 1 mol / L sulfuric acid aqueous solution, stirring for 5 min, adding 6 g of aniline monomer, cooling to 5° C. in an ice water bath, and stirring for 20 min;

[0053] (3) taking 12 g of ammonium persulfate and dissolving it in 100 ml of sulfuric acid aqueous solution, and then adding it to the solution of step (2), and reacting it for 12 h. After the reaction, filtering, washing, and drying are performed to obtain shielding particles B;

[0054] The thermally conductive inorganic filler is one of aluminum nitride and boron nitride.

[0055] The beneficial effect of adopting the above technical solution is that the prepared shielding particles have a high dielectric constant and high dielectric loss, which can effectively realize electromagnetic shielding. At the same time, the core-shell structure prepared by the above coating process has a nano-level shell, which does not affect the thermal conductivity and insulation of its core material filler, while achieving electromagnetic shielding, high thermal conductivity and insulation.

[0056] In some specific embodiments, the epoxy resin is one or a combination of any two of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin, and alicyclic epoxy resin.

[0057] In some specific embodiments, the diluent is one or a combination of any two of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, p-tert-butylphenyl glycidyl ether, trimethylolpropane triglycidyl ether, polypropylene glycol diglycidyl ether, and p-aminophenol triglycidyl ether.

[0058] In some specific embodiments, the pigment is one of carbon black and titanium dioxide or a combination of any two of them.

[0059] In some specific embodiments, the coupling agent is one of vinyl trimethoxy silane, 3-glycidyl propyl trimethoxy silane, 3-aminopropyl trimethoxy silane, 3-mercaptopropyl trimethoxy silane, or any combination thereof.

[0060] In some specific embodiments, the curing agent is one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic anhydride, 2-methylimidazole, N-(3-aminopropyl)imidazole, N,N-dimethylcyclohexylamine, dicyandiamide, and diaminodiphenyl sulfone, or a combination of any two of them.

[0061] In some specific embodiments, the accelerator is one or any combination of imidazole, organic urea, tertiary amine, phosphonium salt, and modified amine.

[0062] In some specific embodiments, the filler is one of aluminum oxide, aluminum nitride, boron nitride, and magnesium oxide, or a combination of any of them.

[0063] A second object of the present invention is to provide a method for preparing the electromagnetic shielding high thermal conductivity bottom filling glue as described above, comprising the following steps:

[0064] Epoxy resin, diluent, pigment and coupling agent are added into a mixing device and stirred and mixed; then filler, shielding particles A and B, curing agent and accelerator are added in sequence and stirred and mixed to obtain the electromagnetic shielding high thermal conductivity bottom filling glue.

[0065] In a specific implementation scheme, epoxy resin, diluent, pigment, and coupling agent are added to a dual planetary power stirring kettle, which is rotated at 30r±10r / min and stirred for 60±10min; filler is added, which is rotated at 30r±10r / min and stirred for 60±10min; shielding particles A and B are added, which are rotated at 30r±10r / min and stirred for 120±10min; curing agent is added, which is rotated at 20r±5r / min and stirred for 30±10min; accelerator is added, which is rotated at 20r±5r / min and stirred for 30±10min to obtain the electromagnetic shielding high thermal conductivity bottom filling glue.

[0066] In a more specific embodiment, epoxy resin, diluent, pigment, and coupling agent are added to a double planetary power stirring kettle, revolved at 30 r / min, and stirred for 60 min; filler is added, revolved at 30 r / min, and stirred for 60 min; shielding particles are added, revolved at 30 r / min, and stirred for 120 min; curing agent is added, revolved at 20 r / min, and stirred for 30 min, and accelerator is added, revolved at 20 r / min, and stirred for 30 min to obtain the bottom filling glue.

[0067] Compared with the prior art, the advantages of the present invention are:

[0068] The present invention uses a conductive polymer as a shell and a heat-conductive inorganic filler as a core material, and forms shielding particles with a core-shell structure through chemical coating. The shielding particles prepared by the present invention have a high dielectric constant and high dielectric loss, and can effectively achieve electromagnetic shielding. At the same time, the core-shell structure prepared by the above-mentioned coating process has a nano-level shell, which does not affect the thermal conductivity and insulation of its core material filler, and simultaneously achieves electromagnetic shielding, high thermal conductivity and insulation. The prepared bottom filling glue has the characteristics of high dielectric constant, high dielectric loss, anti-electromagnetic interference, high thermal conductivity, high dimensional stability, high temperature resistance, high fluidity, etc. DETAILED DESCRIPTION

[0069] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.

[0070] Preparation Example

[0071] The shielding particles A-1 of the present invention are prepared according to the following steps:

[0072] (1) Add 5 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to 100 ml of ethanol solution, stir at 25° C. for 30 min, continue to heat to 60° C., add 10 g of aluminum oxide, stir for 90 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0073] (2) Add 10 g of the filler treated in step (1) to 500 ml of 25% ethanol aqueous solution, stir for 10 min, continue to add 6 g of pyrrole monomer, and cool to 5° C. in an ice water bath;

[0074] (3) Take 6 g of anhydrous ferric chloride, add it to 100 ml of water to dissolve, add it to the solution in step (2), react for 12 hours, filter, wash and dry after the reaction to obtain shielding particles A-1;

[0075] The shielding particles A-2 of the present invention are prepared according to the following steps:

[0076] (1) Add 7 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to 100 ml of ethanol solution, stir at 25° C. for 30 min, continue to heat to 70° C., add 15 g of magnesium oxide, stir for 100 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0077] (2) Add 10 g of the filler treated in step (1) to 500 ml of 25% ethanol aqueous solution, stir for 10 min, continue to add 8 g of pyrrole monomer, and cool to 5° C. in an ice water bath;

[0078] (3) Take 6 g of anhydrous ferric chloride, add it to 100 ml of water to dissolve, add it to the solution of step (2), react for 16 hours, filter, wash and dry after the reaction to obtain shielding particles A-2;

[0079] Shielding particles B-1 is carried out according to the following steps:

[0080] (1) Add 5 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to 100 ml of ethanol solution, stir at 25° C. for 30 min, continue to heat to 60° C., add 10 g of boron nitride, stir for 90 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0081] (2) adding 10 g of the filler treated in step (1) to 100 ml of 1 mol / L sulfuric acid aqueous solution, stirring for 5 min, adding 6 g of aniline monomer, cooling to 5° C. in an ice water bath, and stirring for 20 min;

[0082] (3) Take 12 g of ammonium persulfate and dissolve it in 100 ml of sulfuric acid aqueous solution, then add it to the solution in step (2) and react for 12 h. After the reaction, filter, wash and dry to obtain shielding particles B-1;

[0083] Shielding particles B-2 is carried out according to the following steps:

[0084] (1) Add 3 g of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane to 100 ml of ethanol solution, stir at 25° C. for 30 min, continue to heat to 80° C., add 8 g of aluminum nitride, stir for 70 min, filter, wash and dry after the reaction to obtain a surface-treated thermally conductive inorganic filler;

[0085] (2) adding 10 g of the filler treated in step (1) to 100 ml of 1 mol / L sulfuric acid aqueous solution, stirring for 5 min, adding 5 g of aniline monomer, cooling to 5° C. in an ice water bath, and stirring for 20 min;

[0086] (3) Take 10 g of ammonium persulfate and dissolve it in 100 ml of sulfuric acid aqueous solution, then add it to the solution in step (2) and react for 12 h. After the reaction, filter, wash and dry to obtain shielding particles B-2;

[0087] Example 1

[0088] 10 parts of bisphenol A epoxy resin, 5 parts of naphthalene epoxy resin, 3 parts of 1,4-butanediol diglycidyl ether, 0.5 parts of 3-aminopropyl trimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; 45 parts of alumina were added, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; the shielding particles A-1 were added. 20 parts, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 30r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 120min; 15 parts of methylhexahydrophthalic anhydride are added, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min; 1 part of imidazole accelerator is added, at a revolution stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min to obtain a bottom filling glue.

[0089] Example 2

[0090] 10 parts of bisphenol A epoxy resin, 5 parts of naphthalene epoxy resin, 3 parts of 1,4-butanediol diglycidyl ether, 0.5 parts of 3-aminopropyl trimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; 35 parts of alumina were added, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; the shielding particles A-2 were added. 30 parts, under the conditions of rotation stirring rate of 1000r / min, revolution stirring rate of 30r / min, pressure -0.1~-0.098MPa, temperature of 25℃±5℃, stirring for 120min; add 15 parts of methylhexahydrophthalic anhydride, under the conditions of rotation stirring rate of 1000r / min, revolution stirring rate of 20r / min, pressure -0.1~-0.098MPa, temperature of 25℃±5℃, stirring for 30min; add 1 part of imidazole accelerator, under the conditions of revolution stirring rate of 20r / min, pressure -0.1~-0.098MPa, temperature of 25℃±5℃, stirring for 30min, to obtain bottom filling glue.

[0091] Example 3

[0092] 7 parts of bisphenol F epoxy resin, 8 parts of phenolic epoxy resin, 3 parts of p-aminophenol triglycidyl ether, 0.5 parts of 3-aminopropyl trimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; 35 parts of alumina were added, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; the shielding particles B-1 were added. 30 parts, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 30r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 120min; 17 parts of methyl nadic anhydride are added, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min; 1 part of imidazole accelerator is added, at a revolution stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min to obtain a bottom filling glue.

[0093] Example 4

[0094] 7 parts of bisphenol F epoxy resin, 8 parts of phenolic epoxy resin, 3 parts of p-aminophenol triglycidyl ether, 0.5 parts of 3-aminopropyl trimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; 35 parts of boron nitride were added, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; the shielding particles B-2 were added. 30 parts, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 30r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 120min; 17 parts of methyl nadic anhydride are added, at a rotation stirring rate of 1000r / min, an orbital stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min; 1 part of imidazole accelerator is added, at a revolution stirring rate of 20r / min, a pressure of -0.1 to -0.098MPa, and a temperature of 25℃±5℃, stirring for 30min to obtain a bottom filling glue.

[0095] Comparative Example 1 (Alumina replaces shielding particles)

[0096] 10 parts of bisphenol A epoxy resin, 5 parts of naphthalene epoxy resin, 3 parts of 1,4-butanediol diglycidyl ether, 0.5 parts of 3-aminopropyltrimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0.1 to -0.098 MPa and a temperature of 25°C ± 5°C; 65 parts of alumina were added, and stirred at a rotation stirring rate of 1000 r / min, a revolution stirring rate of 30 r / min, a pressure of -0 .1~-0.098MPa, temperature 25℃±5℃, stirring for 60min; adding 15 parts of methylhexahydrophthalic anhydride, stirring at a rotation stirring rate of 1000r / min, an orbital stirring rate of 20r / min, a pressure of -0.1~-0.098MPa, and a temperature of 25℃±5℃, stirring for 30min; adding 1 part of imidazole accelerator, stirring at an orbital stirring rate of 20r / min, a pressure of -0.1~-0.098MPa, and a temperature of 25℃±5℃, stirring for 30min to obtain the bottom filling glue.

[0097] Comparative Example 2 (conventional product on the market)

[0098] 7 parts of bisphenol F epoxy resin, 8 parts of phenolic epoxy resin, 3 parts of p-aminophenol triglycidyl ether, 0.5 parts of 3-aminopropyl trimethoxysilane and 0.5 parts of carbon black were added into a double planetary power stirring kettle, and stirred for 60 minutes at a rotation stirring rate of 1000r / min, a revolution stirring rate of 30r / min, a pressure of -0.1 to -0.098MPa and a temperature of 25℃±5℃; 65 parts of silicon dioxide were added, and stirred at a rotation stirring rate of 1000r / min, a revolution stirring rate of 30r / min and a pressure of -0. 1~-0.098MPa, temperature 25℃±5℃, stirring for 60min; adding 17 parts of methyl nadic anhydride, stirring at a rotation stirring rate of 1000r / min, an orbital stirring rate of 20r / min, a pressure of -0.1~-0.098MPa, and a temperature of 25℃±5℃, stirring for 30min; adding 1 part of imidazole accelerator, stirring at an orbital stirring rate of 20r / min, a pressure of -0.1~-0.098MPa, and a temperature of 25℃±5℃, stirring for 30min to obtain the bottom filling glue.

[0099] The bottom filling glue prepared in Examples 1-4 and the conventional bottom filling glue prepared in Comparative Examples 1-2 were subjected to the following performance tests respectively, and the measured performance data results are shown in Table 1 below.

[0100] Table 1 Performance data results of Examples 1-4 and Comparative Examples 1-2

[0101]

[0102]

[0103] Here, α1 is the thermal expansion coefficient below TG, and α2 is the thermal expansion coefficient above TG.

[0104] It can be seen from the performance data results in Table 1 that when the shielding particles of the present invention are added, the filler coated with polypyrrole or polyaniline has better compatibility with the resin, the viscosity is reduced, and the fluidity is improved. At the same time, without affecting TG (glass transition temperature), CTE (coefficient of thermal expansion) and volume resistance, the thermal conductivity of the glue is increased by 7 times, the dielectric constant is increased by 5 times, the dielectric loss is increased by 30 times, and the shielding effectiveness is increased by 10-20 times compared with conventional products. The effects of high thermal conductivity, high dielectric constant, high dielectric loss and high shielding effectiveness can be achieved, which is helpful to solve the problems of electromagnetic interference and thermal failure in packaging technology compared with conventional products.

[0105] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An electromagnetic shielding high thermal conductivity bottom filling glue, characterized in that: The composition comprises the following components in parts by weight: The shielding particles A and shielding particles B are particles with a conductive polymer as a shell and a thermally conductive inorganic filler as a core material, which are chemically coated to form a core-shell structure; and the shielding particles A and shielding particles B are not 0 at the same time.

2. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The preparation of the shielding particles A comprises the following steps: (1) adding aminosilane to solvent A, stirring to dissolve, then heating, preferably to 50-80° C., adding thermally conductive inorganic filler A, stirring to react, preferably for 60-120 min, filtering, washing, and drying after the reaction to obtain a surface-treated thermally conductive inorganic filler A; (2) adding the thermally conductive inorganic filler A treated in step (1) to the aqueous solution of solvent A, stirring, continuing to add pyrrole monomer, and cooling to below 10° C.; (3) preparing a catalyst solution, adding it to the solution of step (2), and continuing the reaction, preferably for 12-24 hours. After the reaction is completed, filtering, washing, and drying to obtain shielding particles A; The thermally conductive inorganic filler A is at least any one of aluminum oxide, magnesium oxide, aluminum nitride, and boron nitride.

3. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The preparation of the shielding particles B comprises the following steps: (1) adding aminosilane to solvent A, stirring to dissolve, then heating, preferably to 50-80° C., adding thermally conductive inorganic filler B, stirring to react, preferably for 60-120 min, filtering, washing, and drying after the reaction to obtain a surface-treated thermally conductive inorganic filler B; (2) adding the thermally conductive inorganic filler B treated in step (1) to the aqueous solution of solvent B, stirring, continuing to add aniline monomer, cooling to below 10° C., and stirring for reaction; (3) preparing a catalyst solution, adding it to the solution of step (2), and continuing the reaction, preferably for 12-24 hours. After the reaction is completed, filtering, washing, and drying to obtain shielding particles B; The thermally conductive inorganic filler B is at least one of aluminum nitride and boron nitride.

4. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The epoxy resin is selected from at least any one of bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, hydrogenated bisphenol A epoxy resin, novolac epoxy resin, biphenyl epoxy resin, naphthalene epoxy resin and alicyclic epoxy resin.

5. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The diluent is selected from at least any one of butyl glycidyl ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, p-tert-butylphenyl glycidyl ether, trimethylolpropane triglycidyl ether, polypropylene glycol diglycidyl ether, and p-aminophenol triglycidyl ether.

6. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The pigment is selected from at least any one of carbon black and titanium dioxide.

7. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The coupling agent is selected from at least any one of vinyl trimethoxy silane, 3-glycidyl propyl trimethoxy silane, 3-aminopropyl trimethoxy silane, and 3-mercaptopropyl trimethoxy silane.

8. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The curing agent is selected from at least any one of methyltetrahydrophthalic anhydride, methylhexahydrophthalic anhydride, methylnadic anhydride, tetrahydrophthalic anhydride, hexahydrophthalic anhydride, nadic anhydride, 2-methylimidazole, N-(3-aminopropyl)imidazole, N,N-dimethylcyclohexylamine, dicyandiamide and diaminodiphenyl sulfone.

9. The electromagnetic shielding high thermal conductivity bottom filling adhesive according to claim 1, characterized in that: The accelerator is selected from at least one of imidazole, organic urea, tertiary amine, phosphonium salt and modified amine; and / or The filler is selected from at least any one of aluminum oxide, aluminum nitride, boron nitride and magnesium oxide.

10. A method for preparing the electromagnetic shielding high thermal conductivity bottom filling adhesive according to any one of claims 1 to 9, characterized in that: The following steps are involved: Add epoxy resin, diluent, pigment and coupling agent into a mixing device and stir and mix; then add filler, shielding particles A and B, curing agent and accelerator in sequence and stir and mix to obtain the electromagnetic shielding high thermal conductivity bottom filling glue; Preferably, epoxy resin, diluent, pigment and coupling agent are added to a double planetary power stirring kettle, revolved at 30r±10r / min, and stirred for 60±10min; filler is added, revolved at 30r±10r / min, and stirred for 60±10min; shielding particles A and B are added, revolved at 30r±10r / min, and stirred for 120±10min; curing agent is added, revolved at 20r±5r / min, and stirred for 30±10min, and accelerator is added, revolved at 20r±5r / min, and stirred for 30±10min to obtain the electromagnetic shielding high thermal conductivity bottom filling glue.

Citation Information

Patent Citations

  • A polyaniline-coated composite powder and its preparation method

    CN102260407A

  • Covalent bond grafted polyaniline nanorod array modified carbon-based composite wave absorbing material and preparation method

    CN108341949A

  • Adhesive with double functions of electromagnetic shielding and heat conduction for electronic packaging and preparation method of adhesive

    CN114507497A

  • Low-thermal-expansion high-temperature-resistant chip bottom filling adhesive and preparation method thereof

    CN115678476A

  • Underfill adhesive with low thermal resistance and high thermal conductivity and preparation method thereof

    CN115785868A